2021
DOI: 10.1002/bip.23476
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and applications of peptide nucleic acids selectively binding to double‐stranded RNA

Abstract: RNAs form secondary structures containing double‐stranded base paired regions and single‐stranded regions. Probing, detecting and modulating RNA structures and dynamics requires the development of molecular sensors that can differentiate the sequence and structure of RNAs present in viruses and cells, as well as in extracellular space. In this review, we summarize the recent progress on the development of chemically modified peptide nucleic acids (PNAs) for the selective recognition of double‐stranded RNA (dsR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 95 publications
(142 reference statements)
1
18
0
Order By: Relevance
“…2 Recently, PNAs have also emerged as excellent ligands for triple helical recognition of double-stranded RNA (dsRNA). 2,3 Our research group showed that M-modified triplex-forming PNAs (Fig. 1) bind to dsRNA at least ten-fold stronger than to the same sequence of dsDNA.…”
mentioning
confidence: 97%
“…2 Recently, PNAs have also emerged as excellent ligands for triple helical recognition of double-stranded RNA (dsRNA). 2,3 Our research group showed that M-modified triplex-forming PNAs (Fig. 1) bind to dsRNA at least ten-fold stronger than to the same sequence of dsDNA.…”
mentioning
confidence: 97%
“…It would be interesting to study such structure–light emitting property interactions induced by the E-rotamer through gemdimethyl substitutions, which may change the base stacking interactions. One can also extend the concept by simultaneous introduction of gemdimethyl substitutions at two sites on the backbone or structurally combining with the recently reported bimodal PNAs. The possibility of generating parallel duplexes with selectivity for DNA or RNA may also lead to novel platforms for biomolecular engineering of PNA, affording novel nanoassemblies. The introduction of gemdimethyl substituents also changes the overall hydrophobicity of PNA oligomers, thereby influencing their cell penetration properties, and may lead to newer motifs for molecular assemblies in biomedical applications, in view of the well-documented physicochemical, structural, and biological properties imparted by gem -dimethyl groups in medicinal chemistry …”
Section: Discussionmentioning
confidence: 99%
“…Despite its difficult intracellular transport, it is highly chemically stable, exhibits strong resistance to hydrolytic (enzymatic) cleavage, and does not degrade within living cells. PNA MBs can follow the Watson–Crick hydrogen-bond principles to identify specific sequences of DNA and RNA, and the hybrid compound shows extraordinary thermal stability unique ionic strength effects . PNA MBs can replace common MBs as a probe for target sequence detection.…”
Section: Mbs: Structure Classification and Their Applications In Rna ...mentioning
confidence: 99%
“…PNA MBs can follow the Watson−Crick hydrogen-bond principles to identify specific sequences of DNA and RNA, and the hybrid compound shows extraordinary thermal stability unique ionic strength effects. 60 PNA MBs can replace common MBs as a probe for target sequence detection. Compared to nucleic acids, PNA MBs exhibit superior hybridization properties and improve the chemical and enzymatic stability of nucleic acids.…”
Section: Mbs: Structure Classification and Their Applications In Rna ...mentioning
confidence: 99%